Much ado about nothing? The (non-) politicisation of the European Union in social media debates on migration - Esther Ademmer; Anna Leupold; Tobias Stöhr (European Union Politics, 2019)
The widespread view that the refugee crisis has sparked unprecedented levels of European Union politicisation has rarely been backed by systematic empirical evidence. We investigate this claim using a novel dataset of several thousand user comments posted below articles of German regional media outlets on Facebook. Despite considerable European Union authority in the policy area, extensive media coverage of the crisis and the rise of a populist party in Germany, our results suggest that the politicisation of Europe remains low among social media users, especially when compared to national and subnational levels of governance. When talking about Europe, users hardly refer to European Union institutions or policies. Instead, other member states and notions of the geographic or cultural space dominate the debate.
Keywords: 330; migration; politicisation; public opinion; social media